Structure and interaction of telomeric and telomerase RNA G-quadruplexes. - Martadinata, Herry. (2013)
G-rich oligonucleotides are able to form four-stranded nucleic acid structures called G-quadruplexes in cationic solution. These structures are composed of multiple tetrad planes, in which each tetrad plane consists of four guanines that are Hoogsteen base-paired to one another. Bioinformatics studies across the human genome have found about 376,000 putative G-quadruplex forming sequences. In this work we elucidate the structures and interactions of G-quadruplexes formed by human telomeric RNA (TERRA) and human telomerase RNA sequences.